2021
DOI: 10.3390/molecules26154559
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Structures and Their Hypocholesterolemic Potential

Abstract: Several classes of polysaccharides have been described to have hypocholesterolemic potential, namely cholesterol bioaccessibility and bioavailability. This review will highlight the main mechanisms by which polysaccharides are known to affect cholesterol homeostasis at the intestine, namely the effect (i) of polysaccharide viscosity and its influence on cholesterol bioaccessibility; (ii) on bile salt sequestration and its dependence on the structural diversity of polysaccharides; (iii) of bio-transformations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 128 publications
1
23
0
Order By: Relevance
“…Therefore, uronic acids (contrarily to sulphate groups) may have an important role on GDCA sequestration. Other types of polysaccharides primarily composed of uronic acids have been reported to interact with bile acids [ 43 , 44 ], namely pectins, with a degree of methylesterification of 62% [ 43 ]. Considering that GDCA is negatively charged at the intestinal lumen pH, the interactions behind the negatively charged polysaccharides and bile salts should be mostly due to hydrophobic interactions, possible involving the fucose (a deoxy sugar) present in FCSPs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, uronic acids (contrarily to sulphate groups) may have an important role on GDCA sequestration. Other types of polysaccharides primarily composed of uronic acids have been reported to interact with bile acids [ 43 , 44 ], namely pectins, with a degree of methylesterification of 62% [ 43 ]. Considering that GDCA is negatively charged at the intestinal lumen pH, the interactions behind the negatively charged polysaccharides and bile salts should be mostly due to hydrophobic interactions, possible involving the fucose (a deoxy sugar) present in FCSPs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the TPP-SDF had lower Mw values than MEE- and EE-SDF, mainly because TPP extraction tends to result in low molecular weights of SDF. Previous studies have shown that DF with low molecular weights can more significantly reduce the absorption of cholesterol and promote its excretion in feces [ 39 ]. A lower polydispersity coefficient usually represents a more concentrated and uniform distribution of the molecular weight.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that although carbohydrates constitute a certain amount of melanoidins and all SBMSAV, their structures are quite different from that of natural polysaccharides. This also shows that the formation of hydrogen bonds does not occur easily between the polymeric chains, thus promoting their solubility in water 47 .…”
Section: Micromorphology Particle Size Distribution and Dynamic Visco...mentioning
confidence: 85%